2019
DOI: 10.2141/jpsa.0180135
|View full text |Cite
|
Sign up to set email alerts
|

Blood Testosterone Concentration and Testosterone-induced Aggressive Behavior in Male Layer Chicks: Comparison between Isolated- and Grouped-Raising

Abstract: Testosterone (T) is known to induce aggressive behavior, mainly in male animals. Subcutaneous implantation of T-filled silastic tubes, rather than intramuscular injection of T, is generally recommended for long-term treatment using exogenous T. However, the effect of T implantation on chicken aggressive behavior has not been investigated. In addition, the concentration of T required to induce aggressive behavior or whether rearing conditions such as isolated-or grouped-raising affect T-induced aggressive behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The R-I test was performed at 29 and 30 days of age and the SI test at 31 and 32 days of age. The TAFs and AER were calculated according to the protocols of Raihan et al (2017) and Yan et al (2019). The TAFs are defined as the sum of the frequencies of pecking, biting, kicking, threatening, and leaping.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The R-I test was performed at 29 and 30 days of age and the SI test at 31 and 32 days of age. The TAFs and AER were calculated according to the protocols of Raihan et al (2017) and Yan et al (2019). The TAFs are defined as the sum of the frequencies of pecking, biting, kicking, threatening, and leaping.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that territorial aggression in chickens is T-independent, because the plasma concentration of T in male chicks is reported to be low until 28 days of age ( Tanabe et al , 1979 ). In addition, our latest results showed that the chicks which were castrated and reared in isolation for more than two weeks expressed high frequencies of aggressive behavior ( Yan et al , 2019 ), suggesting that isolation-induced aggressive behavior is also T-independent in chickens. However, the concentration of blood nontesticular T in the castrated chicks, probably derived from the adrenal gland ( Tanabe et al , 1979 ), is approximately 24 pg/ml ( Yan et al , 2019 ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Hormones are known to influence the performance of mating behavior ( Schumacher and Balthazart, 1983 ) and aggression and vary at the individual level, as higher concentrations of endogenous testosterone were observed in quails performing more aggressive behaviors ( Maekawa et al, 2018 ). Aggressive behaviors have been stimulated by the administration of exogenous testosterone ( Erpino, 1975 ; Fernald, 1976 ; Finney and Erpino, 1976 ; Barfield, 1979 ; Ogawa, 1998a ; Graham and Wells, 2001 ; Yan et al, 2019a ), exogenous estradiol ( Grelk et al, 1974 ; Barfield, 1979 ; Trainor et al, 2008 ; Heimovics et al, 2015 ), and the estradiol-testosterone combination ( Archawaranon and Wiley, 1988 ). The hypothalamus is a well-known brain region involved in the performance of aggressive behaviors.…”
Section: Introductionmentioning
confidence: 99%